1973
DOI: 10.1063/1.1680274
|View full text |Cite
|
Sign up to set email alerts
|

On the vibroelectronic Raman effect

Abstract: The theory of a new Raman effect is presented where changes occur in the electronic and vibrational quantum numbers. Theory predicts that such an effect is governed by trace scattering and to first order only totally symmetric vibrations are involved. The experimental data are in good agreement with the theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…(2) The product of representations given in [2] rzfers to the symm9ric and anti-symmetric product and the latter ha-, to be con;idered becau3e we have electronically degenerate states. In an earlier paper [12] it was demonstrated that the tensor of the latter type of transitions is asymmetric, while the tensor of the vibrational transitions is symmetric in the non-resonance case. : componmts of these products can be either symmetric (A,,+E,,) or anti-symmetric ( A z g ) .…”
Section: Raman Selection Rules For Fundamentals In Electronically Degmentioning
confidence: 97%
See 1 more Smart Citation
“…(2) The product of representations given in [2] rzfers to the symm9ric and anti-symmetric product and the latter ha-, to be con;idered becau3e we have electronically degenerate states. In an earlier paper [12] it was demonstrated that the tensor of the latter type of transitions is asymmetric, while the tensor of the vibrational transitions is symmetric in the non-resonance case. : componmts of these products can be either symmetric (A,,+E,,) or anti-symmetric ( A z g ) .…”
Section: Raman Selection Rules For Fundamentals In Electronically Degmentioning
confidence: 97%
“…The tensors belonging to th. [12] If the vibro-electronic Raman effect could contribute to the intensity of the transitions shown in Figure 1, then the tensor is that of species B of C, . At present, however it is not clear to what degree the latter tensors contribute to the intensity of the a,, fundamental in El,.…”
Section: Raman Selection Rules For Fundamentals In Electronically Degmentioning
confidence: 99%
“…Using the dysprosium garnet parameters for In addition, the vibro-electronic Raman effect the initial fit, the splitting patterns for 3~, is only allowed if the symmetries of the electronic of Tm3+ in TlnGaG and TmAlG were calstates are the same (21). Another advantage of culated.…”
Section: Low-lying Electronic Levels and Magnetic Susceptibilities Ofmentioning
confidence: 99%